Takhrij Hadith-Hadith Masyhur dalam Masyarakat Melayu di Malaysia: Usaha ke Arah Membersih dan Memartabatkan Al-Sunnah - Dakir, Jawiah (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2017)
This paper was originally an investigative study focusing on the famous hadith Malays in society. The purpose of this research is to collect the famous hadith (hadits masyhur) in the Malays, then assess the level of hadith to the Malay community concerning the status of hadith which spread among them, especially the fake hadits. The collections of hadits masyhur may be obtained from a variety of sources, such as reading books , local books, magazines, newspaper, jumat speechs, and a collection of recorded religious lectures like Forum Perdana Ehwal Islam Malaysia TV1 and so on. This research employs a critical approach in looking at hadis as the second source of Islamic teaching. It refers to the critical methodology of Hadith scholars who had been instrumental in developing the science of hadith. This study is expected to impose the Islamic community about the importance of sorting hadis which have been implemented among the society in order to apply hadis sahih. Furthermore, Muslims also can avoid the distortions to al-Sunnah or Hadith. Therefore, studying the science of Hadith is strongly important to Muslims, especially among the Malays for keeping the Islamic religion, especially the second source of Islamic teachings, namely al-Sunna or Hadith.